Effect of copper on the antifungal activity of disulfiram (Antabuse®) in fluconazole-resistant Candida strains. (21st February 2022) - Shanholtzer, Claire N; Rice, Cameron; Watson, Katherine; Carreon, Hannah; Long, Timothy E
Abstract: Disulfiram (Antabuse®) is an alcohol use disorder medication that exhibits antifungal activity against Candida species. The purpose of this investigation was to determine if copper potentiates the antifungal effects of disulfiram based on prior observations that the combination demonstrates increased antitumor activity. Our findings revealed that copper addition conferred up to an eight-fold reduction in the minimum inhibitory concentrations (MICs) of disulfiram by broth microdilution assessment. Unexpectedly, copper was also found to nullify the fungicidal activity of disulfiram despite the significant reduction in MICs. It was therefore concluded that copper likely increased the antifungal potency of disulfiram through formation of a fungistatic chelation complex. Lay summary: The effect of copper on the antifungal activity of disulfiram was evaluated against fluconazole-resistant Candida species. The study establishes that copper addition confers greater inhibition of disulfiram-treated Candida cultures, but the combination antagonizes the killing effects of disulfiram.